1980
DOI: 10.1152/jappl.1980.48.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Vital capacity, exercise performance, and blood gases at altitude as related to age

Abstract: Vital capacity (VC) rarely may decrease 35-60% in healthy mountain climbers associated with high-altitude pulmonary edema (HAPE). In the age range 58-71 yr, five of six men during a week or more on White Mt. in 1962 had decreases in VC from 20 to 32% without frank symptoms of HAPE, Dill, one of the five, had decreases in VC again on White Mt. in 1977 and 1978. Yet none of 11 young climbers on White Mt. studied by Hultgren (personal communication) had a significant decrease in VC. Dill's arterial O2 saturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
3
5
0
1
Order By: Relevance
“…Such observations have also been reported by Dill et al [11] and by Coates et al [12] both at high altitude and in a hypobaric chamber, while Jaeger et al [ 13] demonstrated an increased intrathoracic fluid volume in man at 4,300 m, reducing the elastic properties of the lung.…”
Section: Respiratory Volum Es and Flow S At Altitudesupporting
confidence: 70%
“…Such observations have also been reported by Dill et al [11] and by Coates et al [12] both at high altitude and in a hypobaric chamber, while Jaeger et al [ 13] demonstrated an increased intrathoracic fluid volume in man at 4,300 m, reducing the elastic properties of the lung.…”
Section: Respiratory Volum Es and Flow S At Altitudesupporting
confidence: 70%
“…Increased susceptibility to acute mountain sickness among younger persons was also noted by Hackett and colleagues (2). This finding is surprising because some physiologic components of gas exchange that maintain oxygenation, such as vital capacity and hypoxic ventilatory drive, decrease with age (25,26). Although not studied, elderly persons who visit high altitudes for recreational activities may be self-selected to include the more healthy persons who curtail their activities on arrival in ways that decrease the incidence of acute mountain sickness.…”
Section: Discussionmentioning
confidence: 99%
“…Increased susceptibility to acute mountain sickness among younger persons was also noted by Hackett and Rennie [2]. Levine et al [3]and Roach et al [4]both noted that the elderly appear to acclimatize well to 2,500 m. These findings are surprising because some physiological components of gas exchange that maintain oxygenation, such as vital capacity and hypoxic ventilatory drive, decrease with age [1, 5, 6]. Levine et al [3]noted that moderate altitude exposure in the elderly is associated with hypoxemia, sympathetic activation, and pulmonary hypertension resulting in a reduced exercise capacity.…”
Section: Introductionmentioning
confidence: 92%